Repulsive Guidance Molecule b Deficiency Induces Gut Microbiota Dysbiosis and Increases the Susceptibility to Intestinal Inflammation in Mice - Shi, Ying; Zhong, Lu; Li, Yuting; Chen, Yanfang; Feng, Shufen; Wang, Min; Xia, Yin; Tang, Shaohui (Frontiers in Microbiology, 2021)
Imbalance of gut microbiota can induce or aggravate intestinal inflammation. To enhance our understanding of the molecular mechanisms of gut microbiota and inflammatory bowel disease (IBD), we studied the role of RGMb in gut microbiota and colitis in mice. We generated Rgmb knockout mice and inducible Rgmb knockout mice and induced colitis using dextran sulphate sodium (DSS) in these mice. 16S rRNA high-throughput sequencing was performed to acquire the gut microbiota composition and abundance. We found that Rgmb deficiency significantly altered the diversity of gut microbiota and also induced dysbiosis. In sharp contrast to the balanced distribution of various bacteria in control mice, Prevotellaceae was almost exhausted in Rgmb-deficient mice under both basal and inflammatory conditions. Correlation analysis indicated Prevotellaceae was negatively associated with inflammation in Rgmb-deficient mice with colitis. Similar results were obtained at the early inflammatory stage of colitis associated colon cancer (CAC). Taken together, our results reveal that Rgmb deficiency leads to dysbiosis of predominant gut microbiota under basal and inflammatory conditions. Rgmb-deficiency-mediated Prevotellaceae loss may render mice more susceptible to intestinal inflammation. Therefore, RGMb may be a novel potential target for reconstruction of the gut microbiota for the treatment of IBD.